2021
DOI: 10.1021/acs.macromol.1c00534
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Mobility–Stretchability Properties of Naphthalenediimide-Based Conjugated Random Terpolymers with a Functionalized Conjugation Break Spacer

Abstract: To date, few studies of the mobility–stretchability properties of N-type semiconductors, including naphthalenediimide (NDI)-based polymers, have been conducted, and the preparation of intrinsically stretchable N-type semiconducting polymers is very important in the construction of stretchable electronics. In this study, three NDI-based random terpolymers are synthesized by introducing functionalized conjugation break spacers (CBSs) with ester, sulfone, and amide groups. N-type semiconducting polymers with este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…However, the stretchability of conjugated polymers is far lag behind the traditional elastomers. This is because the natural trade-off exists between the mechanical and electronic properties of π-conjugated polymers in a solid-state, since high charge transport requires high crystallinity that will decrease their mechanical robustness. ,, Many strategies have been proposed to enhance the stretchability of conjugated polymers, such as the blending of insulating polymers or elastomers, introducing covalently bonded “flexible spacers” into conjugated backbones, , or importing non-covalent interactions into side chains. , Among these methods, the direct introduction of “flexible spacers” or non-covalent interactions will generate new materials with the synchronously changed crystalline region and amorphous phase, which may significantly affect their photovoltaic properties. The blending of insulating polymer strategy without the complex synthetic process is regarded as the most convenient path to synergistically adjust their mechanical and electronic performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the stretchability of conjugated polymers is far lag behind the traditional elastomers. This is because the natural trade-off exists between the mechanical and electronic properties of π-conjugated polymers in a solid-state, since high charge transport requires high crystallinity that will decrease their mechanical robustness. ,, Many strategies have been proposed to enhance the stretchability of conjugated polymers, such as the blending of insulating polymers or elastomers, introducing covalently bonded “flexible spacers” into conjugated backbones, , or importing non-covalent interactions into side chains. , Among these methods, the direct introduction of “flexible spacers” or non-covalent interactions will generate new materials with the synchronously changed crystalline region and amorphous phase, which may significantly affect their photovoltaic properties. The blending of insulating polymer strategy without the complex synthetic process is regarded as the most convenient path to synergistically adjust their mechanical and electronic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the reported stretchable n-type CPs summarized in Table 3, 18–20,23,42,43 Ran - PNDI2T presents the utmost high mobility retention before its crack-onset strain, and the highest durability after repetitive stretch–release cycles among the n-type CPs in the literatures. Ran - PNDI2T , with a high sequential irregularity in the polymer backbone, has lower crystallinity and enriched chain entanglement, and the more mobile chains are possibly enabled to form tie chains within the crystalline/amorphous domains.…”
Section: Resultsmentioning
confidence: 85%
“…Therefore, researchers in this era are focused on finding an approach to achieve intrinsic stretchability in n-type CPs. A few studies on stretchable n-type CPs have been reported; for example, conjugation breakers with different carbon spacers, 17 functional groups 18 and branched designs 19 were copolymerized with naphthalene–diimide (NDI)-based CPs, and their mobility–stretchability properties were investigated. However, the improved stretchability of CPs usually comes at the expense of charge carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the elastic moduli of the polymers were measured using nanoindentation analysis, and the indentation depth, stiffness, and elastic modulus values were estimated using the Oliver and Pharr method (Figures 4a, S7, Table S2). 47,48 The CDTcontaining polymers show lower elastic moduli (0.309 and 0.568 GPa for r-PCDT-TIC and s-PCDT-TIC, respectively) than those of other typical semiconducting polymers (1−3 GPa). 49,50 Alternatively, the IDT-containing polymers have higher elastic moduli than those of the CDT-containing polymers (1.02 and 2.53 GPa for r-PIDT-TIC and s-PIDT-TIC, respectively), similar to the trend of CCL (010) values.…”
Section: Mechanical Stability Characterizationmentioning
confidence: 99%